Dampak Sosial Ekonomi dari Penggunaan Pinjaman Online Perspektif Maqāṣid al-Syarī‘ah - Azhim, Ikram Kasyful; Natalia, Lisa; Izzati, Syifa Nur; Rizka, Fahala (Al-fiqh, 2025)
This study explores the use of online loans (pinjol) in West Kalimantan through a survey of 11 respondents. Most users are young women aged 20–25 (72.7%) with monthly incomes between IDR 1–3 million (54.5%). The main reasons for borrowing are for consumptive needs (54.5%) and emergencies (27.3%), with SPayLater being the most used platform (81.8%). Reported negative impacts include debt burdens (36.4%), psychological stress (54.5%), and strained social relationships (36.4%). Although 63.6% claim to read the terms and conditions, risk understanding remains low. Furthermore, 63.6% of respondents would not recommend using online loans except in urgent situations. From the perspective of maqāṣid al-syarī‘ah, online lending (pinjol) fails to preserve wealth (ḥifẓ al-māl), life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), lineage (ḥifẓ al-nasl), and even religion (ḥifẓ al-dīn), as it involves elements of riba and exploitative practices. These findings highlight the need for stronger regulations, improved financial literacy, and tighter oversight of illegal lending services. However, these findings remain descriptive in nature and cannot be generalized due to the very limited number of respondents.